Clover-measuring the CMB B-mode polarisation - North, C; Ade, P; Audley, MD; Baines, C; Battye, R; Brown, M; Cabella, P; Calisse, P; Challinor, A; Duncan, W; Ferreira, P; Gear, W; et al. (2007)
We describe the objectives, design and predicted performance of Clover, a fully-funded, UK-led experiment to measure the B-mode polarisation of the Cosmic Microwave Background (CMB). Three individual telescopes will operate at 97, 150 and 225 GHz, each populated by up to 256 horns. The detectors, TES bolometers, are limited by unavoidable photon noise, and coupled to an optical design which gives very low systematic errors, particularly in cross-polarisation. The telescopes will sit on three-axis mounts on a site in the Atacama Desert. The angular resolution of around 8 ́ and sky coverage of around 1000 deg2 provide multipole coverage of 20<ℓ<1000. Combined with the high sensitivity, this should allow the B-mode signal to be measured (or constrained) down to a level corresponding to a tensor-to-scalar ratio of r = 0.01, providing the emission from polarised foregrounds can be subtracted. This in turn will allow constraints to be placed on the energy scale of inflation, providing an unprecedented insight into the early history of the Universe.